2016
DOI: 10.1016/j.joems.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Exact solutions for MHD flow of couple stress fluid with heat transfer

Abstract: This paper aims at presenting exact solutions for MHD flow of couple stress fluid with heat transfer. The governing partial differential equations (PDEs) for an incompressible MHD flow of couple stress fluid are reduced to ordinary differential equations by employing wave parameter. The methodology is implemented for linearizing the flow equations without extra transformation and restrictive assumptions. Comparison is made with the result obtained previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…An attempt has been made to obtain an exact solutions of the problems, by using the wave transformation. A methodology is developed, that not only encompasses the exact solutions that have been appeared in the previous publications [14]. Also, the exact solutions of ( + ) system that do not seem to have been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…An attempt has been made to obtain an exact solutions of the problems, by using the wave transformation. A methodology is developed, that not only encompasses the exact solutions that have been appeared in the previous publications [14]. Also, the exact solutions of ( + ) system that do not seem to have been reported before.…”
Section: Discussionmentioning
confidence: 99%
“…In view of the formulation structure, some limitations of the model problem are the following: The modeled problem is invalid for the flow of gases due to 畏 mentioned in (20), because by the use of viscosity it becomes undefined. Similarly, for S = 0, the problem reduces from unsteady to steady state.…”
Section: Similarity Transformationmentioning
confidence: 99%
“…Results were obtained for the heat transfer with respect to different parameters by the help of shooting method, while the results of previous papers were compared. Furthermore, the influence of MHD on fluid flow in various geometries was studied in [20][21][22]. These are very resent works in the fluid mechanics having MHD flow over thin film with heat and mass transfers.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Hassan et al [5] investigated the effect of temperaturedependent fluid density on a reactive couple stress fluid flowing steadily in a vertical channel saturated with porous materials. Other studies carried out lately that shows the usefulness of couple stress fluid can be found in [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%